IMPACT STABILITY ANALYSIS OF JACKING MACHINE WITH AUTOMATIC FOLLOWING SAFETY DEVICE - AN Yu; HUANG XingYuan; LI Bo; LAI HouJian (Jixie qiangdu)
The hydraulic jacking machine is widely used in mining,construction and other engineering fields. In order to prevent the hydraulic jacking machine from accidents during the jacking process and the equipment failure during the jacking process,it is necessary to add the spacer as the safety device with the jacking up. The height of the work to be carried out is constantly adjusted,which is inconvenient and unsafe. A hydraulic jacking machine with automatic following safety device is designed for this purpose. And the impact stability analysis is carried out with ANSYS LS-DYNA,and the screw combination deflection of the fuse is obtained. The variation law of equivalent stress and the dynamic buckling shape produced by thescrew combination show that the screw combination can withstand the impact of the weight within a certain distance. The maximum distance that can exist between the load-bearing roof and the weight during the jacking process is obtained. It provides a theoretical basis for the design of the jacking machine following control.